TECHNOLOGY-ENHANCED EDUCATION: NURTURING THE DIGITAL GENERATION- EXPERIENCES IN ISLAMIC SCHOOLS IN INDONESIA - Kasmudin Mustapa; Yusdin Bin Mahmudin Gagaramusu; Esther Hesline Palandi; Abdul Wahab Syakhrani; Hadenan Towpek (Adisam Publisher, 2023)
This study delves into the transformative journey of technology-enhanced education within Islamic schools in Indonesia. As the largest Muslim-majority country globally, Indonesia stands at the intersection of tradition and innovation, presenting a unique context for the evolution of Islamic education. This research offers insights into the adoption of emerging technologies, the role of artificial intelligence (AI) and virtual reality (VR), and the preservation of cultural heritage within the Islamic educational landscape. The findings highlight the pivotal role of technology in shaping the future of education, especially in nurturing a digital generation. Online and blended learning, personalized education powered by AI, and immersive VR experiences are revolutionizing the delivery of Islamic teachings. Indonesia's rich cultural diversity adds depth to these experiences as local traditions harmoniously merge with Islamic values. This study underscores the importance of technological integration in Islamic education and emphasizes the need for teacher training, inclusivity, and interfaith dialogue. It also calls for international collaborations to elevate the quality of education. Ultimately, the research emphasizes the alignment of technology with Islamic principles, ensuring that the digital generation emerges with a strong foundation in Islamic teachings, digital literacy, and a deep appreciation for Indonesia's cultural heritage. In today's rapidly evolving world, technology has become an integral part of nearly every aspect of our lives, and its presence in education is particularly profound. This introduction provides a brief overview of the importance of technology in education, emphasizes the significance of technology in the context of Islamic schools in Indonesia, and outlines the purpose and scope of this study.